Bubble fragmentation dynamics in a subsonic Venturi tube for the design of a compact microbubble generator. (June 2021) - Murai, Yuichi; Tasaka, Yuji; Oishi, Yoshihiko; Ern, Patricia
Highlights: Bubble dynamics in a subsonic Venturi was measured with particle tracking velocimetry. Power efficiency was measured based on parametric study changing initial bubble sizes. Bubble fragmentation was explained by a high-speed slip back velocity of bubbles. Theoretical analysis supports the mechanism of fragmentation. Abstract: Microbubble generators are in wide demand in industry following the discovery of a number of new functions of microbubble mixtures. This paper deals with a Venturi tube microbubble generator in which air bubbles at the inlet are fragmented in the diverging part of the tube. In contrast with past studies, we here regulated the flow subsonic so that fragmentation occurred without the help of pressure shock waves. Counting the microbubbles in image processing, we found that a single bubble fragmented into 20–400 microbubbles depending on the Weber number. The power efficiency is found to range from 30 to 50 percent and insensitive to the liquid viscosity. The mechanism of subsonic fragmentation is elucidated adopting particle tracking velocimetry, in association with a theoretical description of the translational motion and the shape oscillation of the bubble. The key event was found to be the bubble's rapid slip-back in the diverging part of the Venturi tube due to a positive pressure gradient. This provides a function that prevents large bubbles from being released from the subsonic Venturi tube.